2006
DOI: 10.1556/avet.54.2006.2.3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of laterality on mastitis incidence in dairy cattle - preliminary study

Abstract: During summer (June to August) of continental weather conditions treated mastitis episodes at a large Hungarian dairy farm were studied to determine the relationship between the distribution of mastitis among quarters of the udder and the lying behaviour (laterality) of the cows. There was a significant difference in laterality between cows that developed mastitis and cows that did not. Cows that developed mastitis, had an increased left laterality in lying, which was related to the increased probability of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…To our knowledge, Hänninen et al (2007) is the only other study to analyze daily steps, and also observed no difference in the number of steps taken during an LPS challenge model. Kikkers et al (2006) determined that cows, which developed naturally occurring mastitis, increased their left side lying behavior with an infection on the right side, as compared with animals that were not infected. Although this observation was related to an increased probability that the cow was infected in her right side, it was not a significant relationship, which is consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, Hänninen et al (2007) is the only other study to analyze daily steps, and also observed no difference in the number of steps taken during an LPS challenge model. Kikkers et al (2006) determined that cows, which developed naturally occurring mastitis, increased their left side lying behavior with an infection on the right side, as compared with animals that were not infected. Although this observation was related to an increased probability that the cow was infected in her right side, it was not a significant relationship, which is consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…aureus (Barkema et al, 1997;Zadoks et al, 2001). This may be explained by the lying behavior of cows (Kikkers et al, 2006) or by transmission via milking machine liners (Zadoks et al, 2001). In contrast, in hand-milked dairy goats, left udder halves are significantly more often infected than right halves, which could be attributed to the fact that most milkers are right-handed and consequently milk the right mammary glands more thoroughly than the left mammary glands (Boscos et al, 1996).…”
Section: Association With Sccmentioning
confidence: 99%
“…However, other studies in horses and cattle found no interaction between lameness and lateralized behavior [76,115,142,145,148]. In contrast, mastitis was found to affect lying side preferences of cows, with one study indicating a more left-sided preference [136] and another study indicating stronger side preferences (141). Bovine respiratory disease was also found to affect lying preferences, although the findings are contradictory, with one study indicating a switch to the left [72] and another study a switch to the right [74] compared to healthy controls.…”
Section: Health Stress and Welfarementioning
confidence: 83%